General Preventive Effect of Flavonoids Isolated from Plants at Experimental Acute Pancreatitis - Singamayum Ashif (African Journal of Environmental Economics and Management, 2024)
With the L-arginine model of experimental pancreatitis (EP), hyperproteinemia, hyperlipidemia, hyperglycemia, hypercholester- olemia, a sharp increase in the activity of digestive hydrolases (α-amylase, lipase, protease complex, active phosphatase) occur. The introduction of flavonoids before the onset of the disease reduced the number of organic substrates and the secretion of hydrolytic enzymes. Therefore, the dysfunction of acinar cells in the pancreas is reduced under the influence of acute pancreatitis. Dihydro- quercetin (DHQ) and Rutins (Rt) showed a more effective antipancreatic effect than Pulicaron (Pl) and Tamiflazid (Tm). During EP, the activity of α-glucosidases (maltase, sucrase) decreased in the mucous membrane of the small intestine, while the activity of β-galactosidase (lactase) did not change. The introduction of Rt, DHQ, Pl, and Tm before EP induction led to the fact that the activity of maltase and sucrase approached normal levels in the mucous membrane and cavity of the small intestine, i.e., in the chyme. The rate of glucose transfer from the small intestine into the blood from the carbohydrate polymer, dimer, and monomers was differ- ent and was expressed at the highest level in disaccharides (maltose and sucrose). In EP, the transition of glucose from solutions of starch, maltose, sucrose, lactose and glucose into the blood decreases depending on the time of incubation in the small intestine. The introduction of flavonoids before the induction of EP increases the transport of glucose into the blood from almost all substrates. Rt and DHQ have a more stimulating effect on the transport of glucose from carbohydrate substrates into the blood, in contrast to Pl and Tm. With EP, occurs edema, infiltration and inflammation, and vacuole degeneration in the pancreatic acini. The constriction of blood vessels observed during the prophylactic effect of Rt, DHQ, and Tm prevented interstitial tissue edema, vacuolization, and general structural tissue disorders. In contrast to Rt, DHQ, and Tm, the prophylactic effect of Pl on the histostructure of the pancreas was not expressed at all.